Automated code for the selection of targets to be observed with the SAINT-EX telescope - Petrucci, Romina Paola (2022)
In this contribution, we present the main characteristics and describe the functioning of the code developed in python language to automatically build the list of objects that are nightly observed in queue mode with the 1-m SAINT-EX telescope.